A conserved, buried cysteine near the P-site is accessible to cysteine modifications and increases ROS stability in the P-type plasma membrane H+-ATPase. Issue 3 (12th February 2021) - Welle, Marcel; Pedersen, Jesper T.; Ravnsborg, Tina; Hayashi, Maki; Maaß, Sandra; Becher, Dörte; Jensen, Ole N.; Stöhr, Christine; Palmgren, Michael
Abstract : Sulfur-containing amino acid residues function in antioxidative responses, which can be induced by the reactive oxygen species generated by excessive copper and hydrogen peroxide. In all Na + /K +, Ca 2+, and H + pumping P-type ATPases, a cysteine residue is present two residues upstream of the essential aspartate residue, which is obligatorily phosphorylated in each catalytic cycle. Despite its conservation, the function of this cysteine residue was hitherto unknown. In this study, we analyzed the function of the corresponding cysteine residue (Cys-327) in the autoinhibited plasma membrane H + -ATPase isoform 2 (AHA2) from Arabidopsis thaliana by mutagenesis and heterologous expression in a yeast host. Enzyme kinetics of alanine, serine, and leucine substitutions were identical with those of the wild-type pump but the sensitivity of the mutant pumps was increased towards copper and hydrogen peroxide. Peptide identification and sequencing by mass spectrometry demonstrated that Cys-327 was prone to oxidation. These data suggest that Cys-327 functions as a protective residue in the plasma membrane H + -ATPase, and possibly in other P-type ATPases as well.